Human complex mixture analysis by “FD Multi-SNP Mixture Kit” - Chen, Anqi; Li, Lun; Zhou, Junfei; Li, Tiantian; Yuan, Chunyan; Peng, Hai; Li, Chengtao; Zhang, Suhua (Frontiers in Genetics, 2024)
Multiple linked single nucleotide polymorphisms (SNPs) have shown potential in personal identification and mixture detection. However, the limited number of marker and sequencing errors have obstructed accurate DNA typing. To develop more candidate loci, the diversity value (D-value) was introduced as a new parameter for screening the novel polymorphic multiple linked-SNP markers, referred to as multi-SNP. In this study, a “FD Multi-SNP Mixture Kit” comprising 567 multi-SNPs was developed for mixture detection. Additionally, a new computational error correction method was applied as a quality control approach for sequencing data. The results demonstrated higher typing success rates than the conventional CE typing method. For single-source DNA, approximately 70-80 loci were detected with a DNA input of 0.009765625 ng. More than 65% of the minor alleles were distinguishable at 1 ng DNA with a frequency of 0.5% in 2- to 4-person mixtures. This study offers a polymorphic and high-resolution detection method for DNA genotyping and complex mixture detection, providing an alternative strategy for addressing challenging mixed DNA traces.